INTERNATIONAL APPROACHES TO THE GOVERNMENT PRICE CONTROL OVER GENERICS AND BIOSIMILARS: A REVIEW - D. G. Tolkacheva; A. V. Torgov; A. S. Margazova (Фармакоэкономика, 2018)
Objective. In this review, we analyzed the policies for price controls on generics and biosimilars in the European Union.Materials and methods. We conducted a literature review regarding government price controls on generics and biosimilars in 28 EU countries and in the Russian Federation.Results. Most of the reviewed countries have policies controlling prices for generic drugs and employ the internal reference pricing. Prices are predominantly determined by setting a discount on the generic price as compared to the price of the original drug. In some countries, the price is set through free competition within the reference group of drugs. However, today’s control of biosimilar pricing in Europe is just building up. A number of countries have no defined procedure for pricing biosimilars, while others utilize the same mechanism as they use for generics, yet with a lower discount. In the Russian Federation, the price control policy is focused on promoting the development and manufacture of generics and biosimilars and, therefore, the discount is lower than the average discount level set in Europe.